PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCURIAN DAN PENGRUSAKAN SARANA BANTU NAVIGASI-PELAYARAN PADA DISTRIK NAVIGASI KELAS III KENDARI - Sofyan Rauf (Yayasan Akrab Pekanbaru, 2019)
The modus operandi carried out in the crime of theft and destruction of the Sailing Navigation Assistance Facility in the Navigation District of Class III Kendari is that theft and destruction is carried out by involving more than 1 person and the crime is carried out in a planned and systematic manner. Law enforcement based on the theft and destruction of Shipping-Navigation Support Facilities has not been in accordance with the regulations in the fields of navigation, institutions, finance, equipment, staffing, and other regulations related to the institutional directorate of navigation.